Investigations of the Mechanical and Microstructural Behaviour of Metal Matrix Composites Reinforced With Graphite and Silicon Carbide - M Divyansh; Dr. Vikas Gadpale; Mr. Abhinav Kumar (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Nowadays composite materials are replacing conventional materials due to their high strength to weight ratio, bio degradable nature, and wear resistance. Aluminium metal matrix composites are gaining widespread acceptance for automobile, aerospace, agriculture farm machinery and many other industrial applications because of their essential properties such as high strength, low density, good wear resistance compared to any other metal. In the present study we deals with the addition of reinforcements such as graphite, fly ash, silicon carbide, red mud, organic material etc. to the aluminium matrix in various proportions. Each reinforced material has an individual property which when added improves the properties of the base alloy. Composite is prepared using liquid metal stir casting process. Micro structural analysis, tensile test, hardness test and wear test were performed to find out the microstructure and mechanical properties of the metal matrix composite. The worn surfaces and wear debris was analyzed using optical microscope. The results of Tensile Test, Brinell Hardness Test and Wear Test for casted composite were plotted and compared with base alloy AA6082. The mechanical properties showed that the increasing the percentage of SiC and Gr particles led to the improvement in tensile strength, hardness and wear resistance upto the certain limit.
Keywords: Aluminium Metal Matrix Composite; Liquid Metal Stir Casting Process; Macro Structural Analysis; Hardness Test; Wear Test